Efisiensi Pemasaran Sapi Bali di Pulau Kabaena Kabupaten Bombana - Sani, La Ode Arsad; Nafiu, La Ode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The research was conducted in the Kabaena island, Bombana District from December 2010 to January 2011. The study aims to analyze the efficiency of marketing channels of Bali Cattle, to calculate the price share received by farmers and the middlemen trader-related marketing efficiency as well as analyze the value of marketing margin of Bali Cattle in Kabaena Island. The research was using the survey method and stratified and purposive sampling was conducted to determine the location of the study. A number of respondents were 30 that determined by simple random sampling with certain criteria. The data obtained were tabulated into a percentage and then reviewed by descriptive analysis. Observed variables are the characteristics of respondents, the sales price, the volume of marketing, marketing costs, marketing agencies, marketing channels and marketing margins of Bali Cattle. he results study showed that: (1) Bali Cattle sold in 2010 reached 189 head (183.2 UT) with the price variation between Rp.4.452.267- Rp.4.690.278 per tail, with the average price, is Rp. 4,571,273 per tails, (2) the efficient marketing channels of Bali Cattle is: farmers → producers → collector on district level → inter-island traders, (3) The highest price received by farmers of Bali Cattle is 87% (the sale of Bali Cattle in collector district level), (4) Bali Cattle marketing margin was highest in the first type of marketing channel (inter-island traders) and the lowest in three types of marketing channels (sub-district level traders).Efficiency, Marketing, Bali Cattle